Covid-19 in Iraq: an estimated cost to treat patients at a private clinic (Journal of Ideas in Health, 2021)
The impact of the COVID-19 pandemic extended to health, social and economic aspects of human life. The international failure to combat this crisis has left many countries suffering under the influence of successive waves of the pandemic. In this report, we present a private medical clinic's experience dealing with the COVID-19 epidemic in Iraq. The adopted protocol to treat COVID-19 patients has briefly been discussed with an estimated cost of treatment in the private sector. We found that most COVID-19 patients recovered from the disease, except for cases that were associated with co-morbidities. The cost of treatment in the private sector is expensive, and most infected people could not afford it without public sector support.
Keywords: Covid-19, Private Clinic, Interleukin-6, Protocol, Estimated Cost, Diyala, Iraq